Genomic Analysis of a Hybrid Enteroaggregative Hemorrhagic Escherichia coli O181:H4 Strain Causing Colitis with Hemolytic-Uremic Syndrome - Angelina A. Kislichkina; Nikolay N. Kartsev; Yury P. Skryabin; Angelika A. Sizova; Maria E. Kanashenko; Marat G. Teymurazov; Ekaterina S. Kuzina; Alexander G. Bogun; Nadezhda K. Fursova; Edward A. Svetoch; Ivan A. Dyatlov (MDPI AG, 2022)
Hybrid diarrheagenic E. coli strains combining genetic markers belonging to different pathotypes have emerged worldwide and have been reported as a public health concern. The most well-known hybrid strain of enteroaggregative hemorrhagic E. coli is E. coli O104:H4 strain, which was an agent of a serious outbreak of acute gastroenteritis and hemolytic uremic syndrome (HUS) in Germany in 2011. A case of intestinal infection with HUS in St. Petersburg (Russian Federation) occurred in July 2018. E. coli strain SCPM-O-B-9427 was obtained from the rectal swab of the patient with HUS. It was determined as O181:H4-, stx2-, and aggR-positive and belonged to the phylogenetic group B2. The complete genome assembly of the strain SCPM-O-B-9427 contained one chromosome and five plasmids, including the plasmid coding an aggregative adherence fimbriae I. MLST analysis showed that the strain SCPM-O-B-9427 belonged to ST678, and like E. coli O104:H4 strains, 2011C-3493 caused the German outbreak in 2011, and 2009EL-2050 was isolated in the Republic of Georgia in 2009. Comparison of three strains showed almost the same structure of their chromosomes: the plasmids pAA and the stx2a phages are very similar, but they have distinct sets of the plasmids and some unique regions in the chromosomes.